2015
DOI: 10.4236/psych.2015.64038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Depression in Patients Undergoing Hemodialysis Due to Renal Failure in Senegal

Abstract: Depression is often encountered with chronic diseases such as renal failure, for which the prognosis has been improved by hemodialysis. The occurrence of depression with these chronic ailments is related to several factors. The aim of this work was to identify risk factors for depression in a population of patients undergoing hemodialysis due to renal failure. We conducted a cross-sectional descriptive study from 1 st January 2012 to 31 st May 2014 in the setting of the hemodialysis unit of the Nephrology Depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…6 The fact that depression is associated with anxiety and/or duration of HD treatment has been found in other studies. 8,35,36 Nevertheless, a previous study found a poor association between depression and duration of HD. 37 Among primary care patients, the comorbidity between depression and anxiety was found at the rate of 15% and the comorbid of anxiety-depressive symptoms was significantly associated with the presence of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 94%
“…6 The fact that depression is associated with anxiety and/or duration of HD treatment has been found in other studies. 8,35,36 Nevertheless, a previous study found a poor association between depression and duration of HD. 37 Among primary care patients, the comorbidity between depression and anxiety was found at the rate of 15% and the comorbid of anxiety-depressive symptoms was significantly associated with the presence of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 94%